Composition of Coffee Beans Influenced by Bioprocessing with Selected Bacteria - Paulina Pakosz; Anna Bzducha-Wróbel; Beata Drużyńska; Ewa Majewska; Rafał Wołosiak (Foods)
Coffee quality can be modified with microorganism addition during post-harvest processing. While most studies focus on yeasts and lactic acid bacteria, other species identified in the digestive tract of palm civets might also contribute to the quality of luwak coffee. Bacteria akin to those identified in palm civets’ gastrointestinal tract or feces were evaluated for their potential to modify coffee bean composition. Among those, Bacillus subtilis ATCC 6633, Gluconobacter sp. KKP 3751 and Lactiplantibacillus plantarum ATCC 4080 exhibited strong growth in green coffee extract. The use of these bacteria significantly changed the amounts of basic coffee components (taste and aroma precursors), and slightly altered bioactive compound levels in green and roasted beans. The influence of fermentation duration was evaluated using L. plantarum. A stationary growth phase and positive changes regarding phenolic content were achieved after 24 h of fermentation. Overall, the use of bacteria can influence bean composition, offering the potential to create unique coffee products.